Matrix Metalloproteinase 9 in Epilepsy: The Role of Neuroinflammation in Seizure Development - Bronisz, Elżbieta (Mediators Inflamm, 2016)
Matrix metalloproteinase 9 is a proteolytic enzyme which is recently one of the more often studied biomarkers. Its possible use as a biomarker of neuronal damage in stroke, heart diseases, tumors, multiple sclerosis, and epilepsy is being widely indicated. In epilepsy, MMP-9 is suggested to play a role in epileptic focus formation and in the stimulation of seizures. The increase of MMP-9 activity in the epileptic focus was observed both in animal models and in clinical studies. MMP-9 contributes to formation of epileptic focus, for example, by remodeling of synapses. Its proteolytic action on the elements of blood-brain barrier and activation of chemotactic processes facilitates accumulation of inflammatory cells and induces seizures. Also modification of glutamatergic transmission by MMP-9 is associated with seizures. In this review we will try to recapitulate the results of previous studies about MMP-9 in terms of its association with epilepsy. We will discuss the mechanisms of its actions and present the results revealed in animal models and clinical studies. We will also provide a comparison of the results of various studies on MMP-9 levels in the context of its possible use as a biomarker of the activity of epilepsy.